2017
DOI: 10.1111/mmi.13694
|View full text |Cite
|
Sign up to set email alerts
|

TgPL2, a patatin‐like phospholipase domain‐containing protein, is involved in the maintenance of apicoplast lipids homeostasis in Toxoplasma

Abstract: Patatin-like phospholipases are involved in numerous cellular functions, including lipid metabolism and membranes remodeling. The patatin-like catalytic domain, whose phospholipase activity relies on a serine-aspartate dyad and an anion binding box, is widely spread among prokaryotes and eukaryotes. We describe TgPL2, a novel patatin-like phospholipase domain-containing protein from the parasitic protist Toxoplasma gondii. TgPL2 is a large protein, in which the key motifs for enzymatic activity are conserved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 67 publications
0
21
0
2
Order By: Relevance
“…4, Table 2). While currently no experimental data are available on the Plasmodium PLPs, a new study in the apicomplexan model parasite Toxoplasma gondii describes an essential role for the PLP TgPL2 (a homolog of Pf3D7_1358000) in maintenance of apicoplast integrity (Lévêque et al, 2017). In the absence of TgPL2, the plastid is rapidly lost and the remaining apicoplasts appear enlarged with abnormal accumulations of membranous structures (Lévêque et al, 2017).…”
Section: Phospholipases Of Plasmodial Parasitesmentioning
confidence: 99%
“…4, Table 2). While currently no experimental data are available on the Plasmodium PLPs, a new study in the apicomplexan model parasite Toxoplasma gondii describes an essential role for the PLP TgPL2 (a homolog of Pf3D7_1358000) in maintenance of apicoplast integrity (Lévêque et al, 2017). In the absence of TgPL2, the plastid is rapidly lost and the remaining apicoplasts appear enlarged with abnormal accumulations of membranous structures (Lévêque et al, 2017).…”
Section: Phospholipases Of Plasmodial Parasitesmentioning
confidence: 99%
“…). Recently, TgPL2 was shown to be critical in maintaining membrane integrity of the apicoplast (Lévêque et al ., ). Lipid analysis revealed that TgPL2 is important for maintaining levels of apicoplast‐generated fatty acids and regulating PC and LPC levels in the parasite.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, compounds identified as potent inhibitors of ExoU PLA 2 activity did not inhibit the activity of mammalian‐derived PLA 2 s (Lee et al ., ). These parasite PLPs will likely be excellent drug targets as TgPL2 has already been characterized as a critical gene to parasite growth and replication (Lévêque et al ., ). Treatment of T. gondii with atglistatin, an inhibitor of ATGL, led to a decrease in parasite replication proportional to drug concentration and disorganization of the parasites within the PV.…”
Section: Introductionmentioning
confidence: 97%
“…All PNPLAs exhibit a catalytic Ser-Asp dyad with the serine residue being embedded within the conserved penta-peptide Gly-Xaa-Ser-Xaa-Gly (GXSXG; reviewed in Arpigny & Jaeger, 1999; Banerji & Flieger, 2004;Ramanadham et al, 2015). Via their phospholipase A 2 (PLA 2 ) activity, PNPLAs are able to generate lysophospholipids and fatty acids, including polyunsaturated fatty acids, which are either further processed within the lipid metabolism pathway or which may act as signalling molecules (Lévêque et al, 2017;reviewed in Kienesberger et al, 2009;Ramanadham et al, 2015;Wilson & Knoll, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such delayed maturation may eventually result in defective gametogenesis, if not fully matured gametocytes have been used in the exflagellation and RBC egress assays.PNPLAs can also be found in the Apicomplexan parasite Toxoplasma gondii; here, three of the roughly six annotated PNPLAs have meanwhile been functionally characterised. The two PNPLAs TgPL1and TgPLA 2 localize to vesicles and are discharged upon immune stress and during invasion, while TgPL2 is crucial for apicoplast integrity(Cassaing et al, 2000;Lévêque et al, 2017;Mordue, Scott- Weathers, Tobin, & Knoll, 2007; reviewed in Tobin & Knoll, 2012). In addition, in other eukaryotes important functions were assigned to PNPLAs.…”
mentioning
confidence: 99%